Religious Harmony as The Gateway To Social Harmony and Peace: An Approach From Lord Buddha And Swami Vivekananda - Mohanta, Dilip Kumar (Philosophy and Progress, 2022)
This short paper argues that interreligious and intra-religious harmony is a necessary condition for social harmony, peace and progress. It is an attempt to develop arguments in favour of the above thesis with special reference to the teachings of Buddha and Vivekananda. Buddha taught human beings to be rational, analytical and moral in way of life. Buddha, therefore, taught openness, interdependence and middle path. Vivekananda also argues for universal religion which is based on scientific, rational and compassionate human relations. He considers that the service of human beings is the service of God. It seems to be a direct impact of the compassionate teachings of Buddha upon Vivekananda. Both of them have indirectly contributed to what is called today the philosophical doctrine of Religious Pluralism which rests on the principle of ‘live and let live’. Both of them were against all kinds of ‘dogmatism, fanaticism and bigotry’. The proposed form of religious harmony is one of the golden ways or middle paths today for addressing many global issues for social harmony, peace and progress. Philosophy and Progress, Vol#67-68; No#1-2; Jan-Dec 2020 P 1-14